The Influence Of Financial Literacy, Financial Technology On Financial Management Behavior Mediated By Behavioral Intention In Generation- Z Of Tualang District Siak Regency - Fasya Puspa Anggreini; Yusrialis (MUI Kota Pekanbaru, 2026)
This study aims to determine the influence of financial literacy,financial technologyon financial management behavior mediated by behavioral intentions in generation Z. The method used is a quantitative method with a techniquepurposive sampling which focuses on Generation Z in Tualang District. Data were collected through a questionnaire using the methodPartial Least Squares Structural Equation Modeling(PLS-SEM) with SmartPLS 4.0 analysis. The number of respondents was 142 people who passed the data quality test. The results of the study showed that financial literacy andfinancial technologyhas a positive and significant influence on financial management behavior. Behavioral intention links financial literacy andfinancial technologywith financial management behavior. This research recommendation emphasizes the importance of financial literacy and technology adoption to encourage Generation Z's financial behavioral intentions.